The Development Status of Sino-Foreign Cooperative Education Programs in Higher Vocational Education Based on Quantitative Data Analysis - Huaming Cheng (Journal of Exploration of Vocational Education, 2025)
On the basis of the program list released by the Ministry of Education in China, there are 893 Sino-foreign cooperative programs in higher vocational education nationwide, with a total enrollment scale of 67,715 students. The regional distribution displays a decrease from the eastern area to the western area on educational programs and enrollment scale. A total of 228 majors are enrolled in the program, among which Accounting is the most popular, followed by Computer Application Technology. The convergence of specialty settings is serious. Jiangsu has the most foreign-partner universities, followed by Zhejiang and Shandong. In the same province, municipality and autonomous region, the number of foreign-partner universities is generally more than that of Chinese partner universities. Foreign partner universities are mainly from Australia, Canada, the United Kingdom and the United States, mainly in developed countries. The development scale of Sino-foreign cooperative programs is closely connected with the development and demand of regional economy. In terms of policy, Sino-foreign cooperative programs in western China and in remote and poor areas should be encouraged. China can combine its own professional advantages with foreign high-quality educational resources to set up characteristic cooperative programs.